catena-Poly[[aquasodium(I)]-μ-[2,2′-(disulfanediyl)bis(pyridine N-oxide)]-μ-(pyridine-2-thiolato 1-oxide)] - B. Ravindran Durai Nayagam; Samuel Robinson Jebas; J. Jebaraj Devadasan; R. Murugesan; Dieter Schollmeyer (Acta Crystallographica Section E, 2010)
There are two monomeric units in the asymmetric unit of the polymeric title compound, [Na(C5H4NOS)(C10H8N2O2S2)(H2O)]n. The NaI ions are six coordinated by four O atoms, one S atom and one water molecule, forming a slightly distorted octahedral geometry. An intramolecular O—H...O hydrogen bond stabilizes the conformation of the molecule. The crystal packing is consolidated by intermolecular O—H...O, O—H...N and O—H...S hydrogen bonds, π–π interactions [with centroid–centroid distances of 3.587 (2) Å] together with weak C—H...π interactions. The molecules are linked into polymeric chains along the b-axis direction.